2023
DOI: 10.1038/s42003-023-05044-1
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the glasshouse plant noble rhubarb (Rheum nobile) provides a window into alpine adaptation

Abstract: Glasshouse plants are species that trap warmth via specialized morphology and physiology, mimicking a human glasshouse. In the Himalayan alpine region, the highly specialized glasshouse morphology has independently evolved in distinct lineages to adapt to intensive UV radiation and low temperature. Here we demonstrate that the glasshouse structure – specialized cauline leaves – is highly effective in absorbing UV light but transmitting visible and infrared light, creating an optimal microclimate for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 148 publications
(193 reference statements)
0
5
0
Order By: Relevance
“…The R. nobile genome was ~1.57 Gb in size, and 99.33% of the sequences were assigned to 11 pseudochromosomes based on Hi-C auxiliary assembly. The higher scaffolding rate of contigs and all four indices (mapping rate, BUSCO, QV and LAI) highlighted the higher quality of our R. nobile genome assembly than recently published R. nobile assembly 56 (Supplementary Table 15 ). To obtain highly reliable gene models, initial gene set were further filtered and a gene set containing 37,770 genes was finally obtained which number close to its close relative buckwheat, and with high functional completeness (>90%).…”
Section: Discussionmentioning
confidence: 75%
“…The R. nobile genome was ~1.57 Gb in size, and 99.33% of the sequences were assigned to 11 pseudochromosomes based on Hi-C auxiliary assembly. The higher scaffolding rate of contigs and all four indices (mapping rate, BUSCO, QV and LAI) highlighted the higher quality of our R. nobile genome assembly than recently published R. nobile assembly 56 (Supplementary Table 15 ). To obtain highly reliable gene models, initial gene set were further filtered and a gene set containing 37,770 genes was finally obtained which number close to its close relative buckwheat, and with high functional completeness (>90%).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, we also detected expansions of Copia/Ale, Gypsy/CRM, and Copia/SIRE in O. digyna and R. nobile Feng2049 (Table S8 ), respectively, which aligned with the unexpected expansion of Gypsy/Tekay, Gypsy/CRM, and Copia/SIRE in R. officinale . The high repeat content is consistently observed in other Rheum species, with percentages ranging from 77 to 87% [ 32 , 33 , 35 , 36 ]. However, in other closely related species, such as F. tataricum (249.3 Mb, 50.96%) [ 98 ], Fagopyrum dibotrys (0.74 Gb, 68.21%) [ 99 ], and O. digyna (219.8 Mb, 39.17%), TE proportions are significantly lower than our focal species.…”
Section: Discussionmentioning
confidence: 58%
“…In Polygonaceae, at least fifteen whole genome sequencing studies have been conducted, with five focusing on the genus Rheum , i.e. Rheum alexandrae [ 32 ], R. nobile [ 33 , 34 ], and two recently published genomes, R. tanguticum [ 35 ] and R. officinale [ 36 ], uncovering large genome sizes of 2.76 Gb and 7.68 Gb, respectively. Analyses of these genomes have identified that three chalcone synthases (CHSs), four CYP, and two β-glucosidases (BGLs) with strong correlations to anthraquinone accumulation in R. tanguticum , alongside 666 candidate genes potentially involved in anthraquinone biosynthesis within the genome of R. officinale .…”
Section: Introductionmentioning
confidence: 99%
“…(4) Despite the great progress towards understanding the ecology of diverse bract types, a deeper understanding of the molecular basis of such variation is needed. Pioneer studies on two 'glasshouse' plants in Qinghai-Tibetan Plateau, Rheum nobile and Rheum alexandrae, have demonstrated that the translucent bracts arise from changes in gene expression involved in abiotic stress resistance in alpine environments (Liu et al, 2013;Feng et al, 2023;Li et al, 2023). Further studies are needed to explore the molecular basis of bract function in diverse plant species, given the diversity of selective agents affecting bracts across different life stages and different plant species, as well as across different habitats.…”
Section: Future Directionsmentioning
confidence: 99%